Ethnic Minority Children‟s Attitudes Towards Competitive Team Members: A Minimal Group Study with British Bengali Children - Lam, Virginia; Moodley, Denzel (Anales de Psicología / Annals of Psychology, 2011)
Since its inception in the late 1990s, the social identity development theory (SIDT; Nesdale, 1999) has been supported by various minimal group studies, although such work has invariably been done with ethnic majority group children. The present study adapted Nesdale et al.‟s (2003) minimal group experiment to test the predictions from SIDT with a sample of ethnic minority children. One hundred and forty-eight British Bengali children aged 5-6, 7-8 and 9-10 years were allocated to a „drawing team‟ that had superior skills than a rival team. The team members were shown to be of the same (Bengali) or a different (white English) ethnicity. Children rated their liking for, and similarity to, their own team and the rival team, and the extent to which they wanted to change teams. It was found that the children preferred their own team members more than the rival team members, irrespective of the ethnic makeup of the teams. However, the children felt more similar to their own team when it was made up of same-ethnic members compared to when it was made up of different-ethnic members. The findings are discussed in relation to those in previous studies with ethnic majority children and support for SIDT.